(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2024)
Objective: We aim to describe factors identified by nurses as challenges and strengths in nursing care for people with wounds in primary health care. Method: This is an exploratory, descriptive, qualitative study conducted from September to November 2022, in the Health District Center of the city of Florianópolis, state of Santa Catarina, Brazil. We used an online questionnaire for data collection, and the results were analyzed based on thematic content analysis according to Bardin. Results: A total of 29 nurses were included in the sample, of which 28 (97%) reported facing challenges as well as identifying strengths in the daily care of individuals with wounds. Based on data analysis, three categories emerged: “Category 1 – Challenges and strengths related to the nurse’s work process”; “Category 2 – Challenges and strengths related to the individual with a wound”; and “Category 3 – Challenges and strengths related to available infrastructure, technological resources, and materials.” Conclusions: The factors highlighted by nurses as strengths and challenges are related to nursing work focused on the person with a wound and to the available infrastructure, technological resources, and materials. Knowledge of these factors can lead to the implementation of tools to overcome challenges and promote strengths, with the aim of improving the quality of this practice.